Analisis Produktivitas Alat Berat pada Tahap Finishing Pekerjaan Jalan STA 0+400-0+500 di Kawasan Industri Subang Smartpolitan Kabupaten Subang - Ihza Khoiruri; Rendy Nafisa Pratama; Moch Alnino Marcelliano Septendiandy; Abdiansyah Prasetya; Muhammad Thoriq Hasan; Firdaus Purnama; Deny Ernawan (Jurnal Sains dan Teknologi, 2026)
Final finishing work is a critical stage in road construction because it affects surface smoothness, elevation accuracy, and road slope in accordance with technical specifications. At this stage, the motor grader serves as the primary piece of equipment; therefore, a productivity analysis is necessary to determine the effectiveness and efficiency of its use in supporting the completion of road construction projects. This study aims to analyze the productivity, equipment requirements, and operational efficiency of the Hidromek MG330 motor grader during final finishing work on the road section STA 0+400-0+500 in the Subang Smartpolitan Industrial Park, Subang Regency. The study employed a quantitative descriptive method, utilizing primary data such as cycle time, number of passes, operating speed, blade working width, pass length, effective working time, and downtime, as well as secondary data including equipment specifications, work volume, and implementation schedules. The results show that the motor grader achieved a productivity rate of 303.33 m³/hour with a daily output of 2,426.64 m³/day. A work volume of 375 m³ can be completed using one motor grader in approximately 1.24 hours, with a working time utilization rate of 15.5% and an operational efficiency factor of 75%. The results of the study indicate that the use of a single motor grader is sufficient to complete finishing work effectively and efficiently and can serve as a reference for planning heavy equipment usage, controlling project timelines, and optimizing productivity in road construction projects.